The hyperthermophilic cystathionine γ‐synthase from the aerobic crenarchaeon Sulfolobus tokodaii: expression, purification, crystallization and structural insights. Issue 3 (1st March 2017) - Sato, Dan; Shiba, Tomoo; Mizuno, Sae; Kawamura, Ayaka; Hanada, Shoko; Yamada, Tetsuya; Shinozaki, Mai; Yanagitani, Masahiko; Tamura, Takashi; Inagaki, Kenji; Harada, Shigeharu
Abstract : Cystathionine γ‐synthase, a pyridoxal 5′‐phosphate (PLP)‐dependent enzyme from the thermoacidophilic archaeon S. tokodaii, was crystallized under three conditions. The structural data suggested that the orientations of the PLP cofactor and the active‐site residues differed among the three forms, which might be key to the activity of the enzyme under extreme conditions. Abstract : Cystathionine γ‐synthase (CGS; EC 2.5.1.48), a pyridoxal 5′‐phosphate (PLP)‐dependent enzyme, catalyzes the formation of cystathionine from anl ‐homoserine derivative andl ‐cysteine in the first step of the transsulfuration pathway. Recombinant CGS from the thermoacidophilic archaeon Sulfolobus tokodaii (StCGS) was overexpressed in Escherichia coli and purified to homogeneity by heat treatment followed by hydroxyapatite and gel‐filtration column chromatography. The purified enzyme shows higher enzymatic activity at 353 K under basic pH conditions compared with that at 293 K. Crystallization trials yielded three crystal forms from different temperature and pH conditions. Form I crystals (space group P 21 ; unit‐cell parameters a = 58.4, b = 149.3, c = 90.2 Å, β = 108.9°) were obtained at 293 K under acidic pH conditions using 2‐methyl‐2, 4‐pentanediol as a precipitant, whereas under basic pH conditions the enzyme crystallized in form II at 293 K (space group C 2221 ; unit‐cell parameters a = 117.7, b = 117.8, c = 251.3 Å) and in form II′ at 313 K (space group C 2221 ; unit‐cell parameters a = 107.5, b = 127.7, c = 251.1 Å) using polyethylene glycol 3350 as a precipitant. X‐ray diffraction data were collected to 2.2, 2.9 and 2.7 Å resolution for forms I, II and II′, respectively. Structural analysis of these crystal forms shows that the orientation of the bound PLP in form II is significantly different from that in form II′, suggesting that the change in orientation of PLP with temperature plays a role in the thermophilic enzymatic activity of StCGS.